Development of a Rat Model of Intra-Amniotic Inflammation via Ultrasound-Guided Administration of a Triggering Agent in the Gestational Sac to Enable Analysis of Individual Amniotic Fluid Samples - Stranik, Jaroslav; Kacerovsky, Marian; Sterba, Martin; Andrys, Ctirad; Abad, Cilia; Staud, Frantisek; Micuda, Stanislav; Soucek, Ondrej; Jacobsson, Bo; Musilova, Ivana (Frontiers in Pharmacology, 2022)
Objectives: To develop a rat model of intra-amniotic inflammation, characterized by concentration of interleukin-6 in amniotic fluid, induced by ultrasound-guided transabdominal administration of lipopolysaccharide into individual gestational sacs. Methods: Ultrasound-guided transabdominal intra-amniotic administration of lipopolysaccharide or phosphate-buffered saline (PBS) as control was performed in rats on embryonic day 18. Only accessible gestational sacs with precise recording of their positions were injected. Twenty-four hours later, individual amniotic fluid samples were collected from gestational sacs of laparotomized animals. Gestational sacs were divided into four subgroups: (i) with lipopolysaccharide: injected gestational sacs from rats undergoing lipopolysaccharide administration; (ii) without lipopolysaccharide: non-injected gestational sacs from rats undergoing lipopolysaccharide administration; (iii) with PBS: injected gestational sacs from rats undergoing PBS administration; (iv) without PBS: non-injected gestational sacs from rats undergoing PBS administration. The concentration of interleukin-6 in individual amniotic fluid samples was assessed using ELISA. Results: In the group of five animals receiving lipopolysaccharide, 24 (33%) and 48 (77%) gestational sacs were and were not injected, respectively. Amniotic fluid was obtained from 21 (88%) injected and 46 (95%) non-injected sacs. In the control group of five animals receiving phosphate-buffered saline, 28 (35%) and 52 (75%) gestational sacs were and were not injected, respectively. Amniotic fluid was obtained from 18 (64%) injected and 50 (96%) non-injected sacs. No labor occurred, and only one fetal death was observed in a gestational sac injected with lipopolysaccharide. Differences in concentrations of interleukin-6 in the amniotic fluid were found among the subgroups of gestational sacs (with lipopolysaccharide: median 762 pg/mL; without lipopolysaccharide: median 35.6 pg/mL; with PBS: median 35.6 pg/mL; without PBS: median 35.6 pg/mL; p < 0.0001). Concentrations of interleukin-6 in the amniotic fluid from gestational sacs with lipopolysaccharide were higher than those in the three remaining subgroups (p < 0.0001). No differences in concentrations of interleukin-6 in the amniotic fluid were identified between the three remaining subgroups. Conclusion: Ultrasound-guided transabdominal intra-amniotic administration of lipopolysaccharide with subsequent collection and analysis of amniotic fluid samples is feasible in rats. Intra-amniotic administration of lipopolysaccharide led to the development of intra-amniotic inflammation without leading to fetal mortality or induction of labor.